25 years of the Workers' Bank : including report for 1946. - The Workers' Bank Limited (Tel-Aviv, 1947)
Bibliotheek Camille Huysmans
Engels
Brochure
Keywords: joodse arbeidersbeweging; zionisme; banken; Palestina